2019
DOI: 10.22616/rrd.25.2019.081
|View full text |Cite
|
Sign up to set email alerts
|

Content marketing decisions for customers’ desired value in the tourism sector

Abstract: In a landscape of increasing customer/firm interactions in digital space, content marketing, which aims to generate prospects and sales to foster customers' brand engagement, brand awareness and trust, is on the rise. Notwithstanding, despite significant marketing specialist interest, scientific content marketing research is not widely developed. Therefore, it encourages the need for new studies in the content marketing field. This paper introduces theoretical and practical aspects of content marketing decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Regarding the approach/area of content marketing specifically, the study of the publications revealed different approaches. Most authors perceive content marketing as a marketing strategy (Radenković-Šošić, 2013;Rastokaitė, 2016;Repovienė, 2017;Repovienė and Pažėraitė, 2019;Salminen et al, 2019;Wilcock, 2018;Wagner and Boatright, 2019). Other authors perceive content marketing as a marketing method (Wall and Spinuzzi, 2018), the art of communication (Poradova, 2020), or a marketing technique (Halevi and O'Hanlon, 2016).…”
Section: Area Of Content Marketingmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the approach/area of content marketing specifically, the study of the publications revealed different approaches. Most authors perceive content marketing as a marketing strategy (Radenković-Šošić, 2013;Rastokaitė, 2016;Repovienė, 2017;Repovienė and Pažėraitė, 2019;Salminen et al, 2019;Wilcock, 2018;Wagner and Boatright, 2019). Other authors perceive content marketing as a marketing method (Wall and Spinuzzi, 2018), the art of communication (Poradova, 2020), or a marketing technique (Halevi and O'Hanlon, 2016).…”
Section: Area Of Content Marketingmentioning
confidence: 99%
“…The findings suggest that content marketing is essential, and the most important are (co)creation and distribution of information. Finally, the study of the aims of content marketing revealed that it is vital to make a decision (Järvinen and Taiminen, 2016;Tsiakali, 2018;Mansour and Barandas, 2017), retain customers (Radenković-Šošić, 2013), build loyalty (Radenković-Šošić, 2013;Du Plessis, 2017c), provide benefits (Repovienė and Pažėraitė, 2017;Turon and Juzek, 2015;Repovienė and Pažėraitė, 2019), and build credibility (Wagner and Boatright, 2019). It can be stated that the results (outcomes) of content marketing are essential, and it is most important to provide benefits and decision making.…”
Section: Aims Of Content Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…While traditional marketing and advertising is still present, digital marketing and advertising is growing much more rapidly. In the digital marketing sphere, content marketing is a way for customers to take the initiative in looking for product information and also represents an opportunity for hospitality and travel marketers to curate meaningful materials for them [42,43]. The Content Marketing Institute (CMI) (2014) defined content marketing to be "a strategic marketing approach focused on creating and distributing valuable, relevant, and consistent content to attract and retain a clearly-defined audience-and ultimately, to drive profitable customer action".…”
Section: Content Marketing and Co-creationmentioning
confidence: 99%
“…Contudo, Gundlach (2007) O conceito de marketing de conteúdo visa atrair e reter os clientes por intermédio de produções e distribuições de conteúdos exclusivos, relevantes, valiosos, bem produzidos e divertidos. Por outro lado, destaca-se que as empresas devem se atentar a confiabilidade dos seus itens publicados (Repovienė & Pažėraitė, 2019).…”
Section: Dinâmicasunclassified